TRAFFICKING AS A MAJOR SOCIAL ISSUE: RETHINKING THE MANAGEMENT POLICY AND PRACTICES TO FACE THIS PHENOMENON, WITH THE IMPLEMENTATION OF PROJECTS ORIENTED ORGANIZATIONAL STRUCTURES AND STRATEGIC PROCESSES - Patta, Efthimia; Uslu, Ferit; Koffas, Stefanos; Sdrolias, Labros; Papadimopoulos, Ioannis; Rolínek, Ladislav; Aspridis, Georgios; Škodová Parmová, Dagmar; Gkountroumpi, Evangelia (OCERINT Publishing, 2015)
The multidimensional phenomenon of trafficking and specifically trafficking in human beings for sexual purpose is a major social problem in a domestic and international level. The conception of that issue is rooted in the participants' interest about the size and intensity of this phenomenon in a country that is plagued by a strong economic and social crisis, Greece, where it now seems infeasible to use effective coping mechanisms during this growing situation, so sexual trafficking, causes today a number of ethical, social, cultural and ethnic issues. This paper starts with a thorough literature review as the introductory step of reference, understanding and consolidate this phenomenon and continues with scientific recording and evaluating all the parameters that generate it. Additionally, this paper collects information and utilizes research results regarding in approach policies and management practices of the responsible government agencies and NGOs to date, and finally proposes the implementation of specialized organizational structures oriented projects and innovative operational and communication procedures as the best practice of dealing with the difficult and uncertain conditions prevailing in that country.
Keywords: Sexual Trafficking; Range and Intensity of the Phenomenon; Management Policy; Management Practices; Organizational Structures; Strategic Processes; Uncertainty Conditions; Greece